Distribution Patterns of Polyphosphate Metabolism Pathway and Its Relationships With Bacterial Durability and Virulence - Wang, Liang; Yan, Jiawei; Wise, Michael J.; Liu, Qinghua; Asenso, James; Huang, Yue; Dai, Shiyun; Liu, Zhanzhong; Du, Yan; Tang, Daoquan (Frontiers in Microbiology, 2018)
Inorganic polyphosphate (polyP) is a linear polymer of orthophosphate residues. It is reported to be present in all life forms. Experimental studies showed that polyP plays important roles in bacterial durability and virulence. Here we investigated the relationships of polyphosphate (polyP) with bacterial durability and virulence theoretically. Bacterial lifestyle, environmental persistence, virulence factors, and species evolution are all included in the analysis. The presence of seven genes involved in polyP metabolism (ppk1, ppk2, pap, surE, gppA, ppnK, ppgK) and 2595 core virulence factors were verified in 944 bacterial reference proteomes for distribution patterns via HMMER. Proteome size and virulence factors were compared in terms of gain and loss of polyP pathway. Literature mining and phylogenetic analysis were recruited to support the study. Our analyses revealed that presence of polyP metabolism is positively correlated with bacterial proteome size and the number of virulence genes. A potential relationship of polyP in bacterial lifestyle and environmental durability is suggested. Evolutionary analysis shows that polyP genes are randomly lost along the phylogenetic tree. In sum, based on our theoretical analysis, we confirmed that bacteria with polyP metabolism are associated with high environmental durability and more virulence factors.